2019
DOI: 10.1186/s12888-019-2238-9
|View full text |Cite
|
Sign up to set email alerts
|

An Asian study on clinical and psychological factors associated with personal recovery in people with psychosis

Abstract: Background Despite the rising recognition of personal recovery, there is a lack of research on personal recovery in individuals with psychosis in Singapore. This study aims to evaluate the psychometric properties of the QPR-15 using the CHIME personal recovery framework and to examine its associations with clinical recovery factors. Methods Sixty-six stable outpatients were recruited and assessed at two time points approximately 2 weeks apart. Convergent validity was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 66 publications
4
23
0
Order By: Relevance
“…This is noteworthy, since these variables were not based on the service users’ self-reports but were rated by research assistants. Symptom reduction is generally regarded as clinical recovery, but earlier research has also highlighted that it can be important for personal recovery, though decreased symptoms are not the primary focus for the overall personal recovery journey [ 8 ]. As this is in line with our findings, it could be warranted for future research to explore further the relationship between clinical and personal recovery.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is noteworthy, since these variables were not based on the service users’ self-reports but were rated by research assistants. Symptom reduction is generally regarded as clinical recovery, but earlier research has also highlighted that it can be important for personal recovery, though decreased symptoms are not the primary focus for the overall personal recovery journey [ 8 ]. As this is in line with our findings, it could be warranted for future research to explore further the relationship between clinical and personal recovery.…”
Section: Discussionsupporting
confidence: 93%
“…Using the QPR [ 34 ] to measure recovery in this study can be seen as a strength, since it aligns well with CHIME, one of the most-used frameworks for personal recovery in mental health services today [ 10 ]. Research shows that the QPR incorporates all the concepts in the CHIME framework [ 8 , 44 ]. Some limitations need to be acknowledged, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, considering the overlap, the associations between PR-scale total scores and the CHIME dimensions were medium to large. This overlap is confirmed by the fact that some studies investigated PR-scale total scores in relation to CHIME dimensions in order to assess the convergent validity of a PR measure ( 21 , 25 , 30 , 31 , 40 , 41 , 49 ).…”
Section: Discussionmentioning
confidence: 89%
“…For instance, a recent longitudinal study exploring psychological predictors of PR found that less negative beliefs about self and hopelessness along with higher self-esteem were stronger predictors of PR than psychotic symptoms or functioning (Law et al, 2016). Other research has focused on factors incorporated in the CHIME model, such as hope in relation to PR in psychosis (Lim et al, 2019). However, based upon the model these factors are components of PR as opposed to psychological correlates/predictors of PR (Leamy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%